Baseline knowledge of female genital fistula symptoms, causes and treatment among a rural population in Northern Bangladesh - Saha, Stacy; Ambauen-Berger, Bea; Munira, Shirajum (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To provide baseline information among the general population on knowledge regarding female genital fistula (FGF) prior to media campaigns and diagnostic camps in 30 unions of 8 districts in Northern Bangladesh. Introduction: The aim of the Bangladesh national strategy is to end fistula by 2030. According to the Maternal Morbidity Validation Study approximately 19,755 women lived with obstetric fistula in 2016. Poor understanding of FGF and how it is treated hinders case finding of those needing treatment. Methods: The survey was conducted in Kurigram District. Out of a total sample of 500, 380 (76%) were chosen from every 5th household of a randomly selected village on high land and 120 (24%) were all households of two river islands. Results: The respondents were 83.4% female and 16.6% male. The mean age was 36.2 years of age, ranging from 17 to 85; 58.6% had no formal education and 61% reported a family income of less than Tk 6000/ month. Overall 12% of participants had heard of FGF (‘a condition with leaking of urine and/or feces’), 13% of those living on high land and 7.5% of those living on river islands (p<0.1). 98.2% of respondents could not name any cause of FGF; 90.6% could not name any symptom and only 7 (1.4%) knew that surgery is the only cure. Conclusions: Knowledge of FGF is low among the public in rural Bangladesh, especially remote areas. Campaigns to disseminate messages on FGF could contribute to case finding of affected women.